Room temperature synthesized GaAs quantum dot embedded in SiO2 composite film - Lee, Sunghun; Shin, Dong Wook; Kim, Won Mok; Cheong, Byung-ki; Lee, Taek Sung; Lee, Kyeong Seok; Cho, Sunghun (ELSEVIER SCIENCE SA, 2006)
Nano-composite films, consisting of GaAs quantum dots embedded in SiO2 glass matrix, were fabricated and analyzed in terms of their structural, chemical, and optical properties. In order to fabricate uniformly dispersed GaAs quantum dots in the SiO2 matrix, composite films consisting of alternate layers of GaAs and SiO2 Were deposited in the manner of a superlattice by radio frequency magnetron sputter deposition. In order to control the size of GaAs quantum dots the thickness of GaAs in individual layers was varied at a fixed GaAs total volume fraction. Transmission electron microscopy and X-ray photoelectron spectroscopy analyses revealed that GaAs quantum dots were in crystalline phase and in the form of a Ga-As compound. From optical absorbance measurements, absorption edges at visible wavelength band were determined and compared among composite films of varying GaAs nominal thickness. The amount of blue shift of the absorption edge increased with decreasing GaAs nominal thickness, i.e. quantum dots size. Band gaps of the composite films determined from Tauc plots and photoluminescence measurements exhibited a linear decrease with increasing GaAs nominal thickness. Large values of third-order non-linear optical susceptibility chi((3)) (similar to 7.6 x 10(-14) m(2)/V-2 at 488 nm), which were believed to originate due to the state filling effect, were observed. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: NANOPARTICLES; MICROCRYSTALLITES